A Comparative Sociolinguistic Study of Archaic Forms that Decline in Indonesian and Early Modern English - Azarian, Andyka Ariella Keanu; Aminullah,; Aziz, Muhammad Syahrul; Reswara, Sandy (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The purpose of this research is to analyze the decline of archaic forms between Indonesian and Early Modern English Language. The approach used in this research is sociolinguistic with a qualitative comparative method for studying language evolution in society and historical context. The data research has been collected from various sources, including historical texts, literary works, and a language corpus that are relevant to related topics. Research findings have shown that the trend toward simplification in the form of pronouns is one of the main indicators of the decline of archaic Indonesian and English. In addition, these changes are also affected by various social factors, such as society's structural changes, language contact, and the development of communication culture. The contribution of this research lies in providing cross-cultural evidence regarding the dynamics of change in both languages, particularly in understanding how and why archaic forms of both languages are used in the modern era in their use.